Implementasi Kebijakan Perlindungan Hukum terhadap Hak-Hak Narapidana di Rutan Kelas IIB Kuala Kapuas Kal-Teng - Fitri Fitri (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2015)
The government of Republic of Indonesia undertake pemajuan, penghormatan, protection, fulfillment, and enforcement effort of human rights to convicts who are in penitentiaries and correctional facilities through Correctional System as has been established in Law Number 12 Year 1995 on Correctional Institution. Based on this act, various regulation of execution related to Correctional process issued by the government as the form of correctional system operatinalization which is considered as effective implementation and as realization of the government’ responsibility in respecting, protecting, enforcing and promoting human rights as stated in article 71-72 Law Number 39 Year 1999 on Human Rights. Besides the law, correctional institution becomes indicator of protection and fulfillment of human rights. This method used in this research is qualitative method in which it is expected to result in deep analysis about utterance, writing and behaviours which can be observed from an individual, group, society and particular organization in particular context, which is analyzed from the whole, comprehensive, and holistic point of view. (Hadjr, 1996 in Basrowi and Sudikin, 2002:2)The findings of this research are the followings: (1) Right protection in performing the religion, namely the existence of mosque and church provided by the penitentiary supports the religious activity in Class IIB of Kuala Kapuas penitentiary, Central Kalimantan, (2) Legal protection on the right of getting health service, namely by the supervision or the convicts’ clothes maintenance done by penitentiary officers, and the health checking for the convicts in Class IIB of Kuala Kapuas Penitentiary is done by having cooperation with doctors and health centres, (3) Legal protection on the visit of convicts’ families, namely the visit is done in six days, Monday, Tuesday, Wednesday, Thursday, Friday, Saturday, from 08.00 to 13.00 WIB in visit lounge and the visit is limited for fifteen minutes (4) Factors which encourage and detain the law on the convicts’ rights should be revamped. In fact, the penitentiary officers has done maximum effort to give service in Class IIB of Kuala Kapuas Penitentiary Central Kalimantan. Keywords: right, protection, convict